Development of Smart Controlled Precision Motorized Positioning System - Mohd Shukri, Nor Nabila Aisyah; Ali, Ahmad Hadi (Enhanced Knowledge in Sciences and Technology, 2023)
Motorized stage is generally a foundation to a certain application such as laser, CNC machine, 3D printing and microscope. Operational CMS controlled by humans can lead to human error and hazard while working. Applications such as lasers can be harmful to people working in high power laser fields. The hazardous of laser including handling the laser while micro-position the laser. WCMS consists of four main parts which are the mechanical stage, motor driving circuit, software controller and interfacing device. The mechanical stage x-axis sliding table was designed and developed. The material of the mechanical stage is aluminum. The motor driver of WCMS is L298N motor driver and was used by the NodeMCU 2688 controller for the WMS. The system was powered by 12V and 3A power supply. Smartphones were also used to control the WCMS using Wi-Fi and a Blynk application was used for the interface. blink and not MCU microcontroller. WCMS can be operated anywhere, as long as the smartphone and the WCMS is connected to the Internet. As the stepper motor is moved, the stage of WCMS also experiences a move. As for 1, 5, 25, 50, 100 and 200 revolutions per minute, the time taken for the stage is 70, 15, 3.7, 2.2, 1.3 seconds respectively.